Evaluating Endovascular Strategies for Carotid Blowout Syndrome: A Retrospective Analysis at a Single Institution - Abramyan, Arevik; Samaan, Mena; Gupta, Gaurav; Sozio, Stephen J.; Sundararajan, Srihari; Roychowdhury, Sudipta (Journal of Clinical Interventional Radiology ISVIR, 2025)
Carotid blowout syndrome (CBS) is a life-threatening complication predominantly associated with head and neck malignancies. The high morbidity and mortality rates necessitate effective management strategies. This study evaluates the efficacy and safety of endovascular interventions in managing CBS.We conducted a retrospective analysis of endovascular treatments for CBS performed at our institution from 2016 to 2023. Data on patient demographics, cancer types, previous treatments, and specific CBS characteristics were collected. Outcomes measured included procedural success, posttreatment complications, and mortality rates.The study included 19 patients with a mean age of 56.7 ± 11.15 years, predominantly male. Lesion locations included internal carotid arteries (ICAs) (42.1%), common carotid arteries (36.8%), and external carotid arteries (21.1%). CBS presentations were classified as threatened (26.3%), impending (42.1%), and acute (31.6%). Endovascular procedures included coil occlusion with Micro Vascular Plug (MVP) systems (31.6%), standalone coil occlusion (21.1%), covered stent placement (15.8%), polyvinyl alcohol embolization particles (15.8%), standalone MVP occlusion (10.5%), and MVP occlusion with a flow diverter and covered stent (5.3%). Technical success was achieved in all cases. Intraoperative rerupture occurred in one patient. Postprocedural complications included stroke (10.5%), rebleeding (10.5%), infection (10.5%), and carotid sinus syndrome (5.3%). The mortality rate before discharge was 21.1%, primarily due to cancer-related causes. Importantly, one of the deaths was procedure-related, occurring as a result of a stroke following thrombosis at the repair site.Endovascular treatments for CBS offer promising outcomes, characterized by high technical success, and provide viable alternatives to traditional surgical interventions. While these minimally invasive techniques effectively control hemorrhage, it is important to consider the associated complication rates, which necessitate careful patient selection and thorough procedural planning. Despite the challenges posed by the advanced nature of underlying malignancies, the adoption of a multidisciplinary approach is critical to optimize outcomes in CBS management.
Keywords: carotid blowout syndrome; endovascular interventions; flow diverter devices; head and neck oncology